PENGEMBANGAN KEMASAN PRODUK PAPER CUP TAKE AWAY MENGGUNAKAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DI HOMWOK KOPI - Yose Rizal Taufiqurrahman; Aranza Rifqi Diemsy; Arief Eka Kurniawan; Aditia Rahmana; Diaz Arjun Annolu; Ayudyah Eka Apsari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Indonesian coffee market is experiencing rapid growth, driven by the rising popularity of coffee consumption and the take-away culture. Consequently, the demand for practical, eco-friendly, and recyclable packaging is also increasing. The same applies to Homwok Kopi, which prompted this study to develop an optimal design for take-away paper cup packaging using the Quality Function Deployment (QFD) method. The results revealed that the proposed take-away paper cup packaging will use 350 gsm ivory paper material with dimensions of 59 cm in length, 22 cm in width, and a weight of 20 grams. An innovative locking mechanism for smaller cups will be incorporated to ensure the cups remain stable within the packaging, minimizing spillage during movement. The design features a combination of broken white and blue colors, along with a handle that is comfortable to grip.